Anatomy of an alibi [large type] - Elston, Ashley (Random House Large Print, 2026)
Two women with separate motives agree to temporarily exchange identities in order to uncover hidden truths within a marriage marked by secrecy and control. When the husband at the center of their plan is found murdered, both women must navigate the consequences of deception and conflicting alibis. Set in Louisiana, the novel explores themes of identity, trust, and betrayal through a suspense-driven narrative focused on psychological tension and shifting perspectives.